Equality? The Importance Of Gender Mainstreaming Policies (Journal of Namibian Studies : History Politics Culture, 2023)
As a country with a large population and diverse ethnicities and cultures as well as religions, Indonesia needs to optimize gender equality through gender mainstreaming policies. Issues related to discrimination and gender disparity still occur in the realm of politics and women's leadership in various fields. Policy is an important factor to be prioritized in the development of gender mainstreaming in Indonesia which is interesting for further study. The results of the data analysis showed that there was no specific policy on gender mainstreaming yet. In addition, several laws did not have operational, institutional, and legal instruments in their implementation. Differences in the meaning of gender and gender mainstreaming can also be found in the policies issued by the government. However, the government's efforts to allocate a gender-based budget support the implementation of gender mainstreaming which involves various stakeholders from the central government to local governments in Indonesia.